2020
DOI: 10.3390/brainsci10120902
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Wnt Signalling in the Alzheimer’s Brain

Abstract: The Wnt signalling system is essential for both the developing and adult central nervous system. It regulates numerous cellular functions ranging from neurogenesis to blood brain barrier biology. Dysregulated Wnt signalling can thus have significant consequences for normal brain function, which is becoming increasingly clear in Alzheimer’s disease (AD), an age-related neurodegenerative disorder that is the most prevalent form of dementia. AD exhibits a range of pathophysiological manifestations including aberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 274 publications
(354 reference statements)
1
26
0
Order By: Relevance
“…Importantly, ApoE, a major genetic risk factor for AD, promotes the degeneration of endothelial cells and hampers the clearance of Aβ exerted by pericytes. Moreover, brain endothelial cells connected by tight junctions and their main constituents, claudins, are Wnt/β-catenin target genes [ 241 ]. In line with this, Wnt7a and β-catenin knockouts in adult mice decreased the expression of claudins, which was accompanied by inflammation, insults to the CNS vasculature, and the dysregulated BBB maintenance.…”
Section: Wnt Signaling In Ischemic Brain Injury and Alzheimer’s Diseasementioning
confidence: 99%
“…Importantly, ApoE, a major genetic risk factor for AD, promotes the degeneration of endothelial cells and hampers the clearance of Aβ exerted by pericytes. Moreover, brain endothelial cells connected by tight junctions and their main constituents, claudins, are Wnt/β-catenin target genes [ 241 ]. In line with this, Wnt7a and β-catenin knockouts in adult mice decreased the expression of claudins, which was accompanied by inflammation, insults to the CNS vasculature, and the dysregulated BBB maintenance.…”
Section: Wnt Signaling In Ischemic Brain Injury and Alzheimer’s Diseasementioning
confidence: 99%
“…(ii) tau protein hyper-phosphorylation process that involves GSK3β and Dikkopf 1 (DKK1), and generates neurofibrillary tangles within neurons; (iii) hippocampal-dependent cognitive impairment [73][74][75].…”
Section: Ion Channels and Wnt Signaling Regulation In Neurodegeneration And Neurological Diseasesmentioning
confidence: 99%
“…In AD, Wnt signaling impairment accelerates the onset of the disease and provokes the development of three AD hallmarks: (i) the production and aggregation of β-amyloid; (ii) tau protein hyper-phosphorylation process that involves GSK3β and Dikkopf 1 (DKK1), and generates neurofibrillary tangles within neurons; (iii) hippocampal-dependent cognitive impairment [ 73 , 74 , 75 ].…”
Section: Channels-wnt-dependent Signaling Axes In Diseasesmentioning
confidence: 99%
“…In addition, Wnt signaling was found to be dysregulated in Alzheimer’s disease. 8 A recent study showed that increased Wnt signaling is associated with colorectal cancer. 9 On the basis of these results, Notum appears as an important therapeutical target for a number of diseases.…”
Section: Introductionmentioning
confidence: 99%